Preparation and application of ferric citrate modified Amberlyst 36 resin
Patent Information
- Application Number
- CN202611085734.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-20
AI Technical Summary
1.本发明采用醇分散浸渍法制备柠檬酸铁改性Amberlyst 36树脂,制备工艺简单、条件温和、无二次污染,易于工业化放大;通过调控柠檬酸铁负载量和添加连接剂,既保留了Amberlyst 36树脂原有磺酸基(-SO3H)骨架的完整性,又引入羧基(-COOH)、Fe-O基团作为新增活性位点,形成磺酸基与柠檬酸铁活性位点的双位点结构,保证了新增活性位点的数量,同时还避免了过量柠檬酸铁团聚堵塞树脂孔道,实现了树脂孔结构与活性位点的最优匹配。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of ion exchange resin modification and wet phosphoric acid purification technology, and particularly to the preparation and application of ferric citrate modified Amberlyst 36 resin. Background Technology
[0002] Driven by the global "dual-carbon" strategy, the new energy industry is developing rapidly. Lithium iron phosphate (LiFePO4), as the core cathode material for power batteries in new energy vehicles and large-scale renewable energy storage devices, is experiencing a continuous increase in market demand. High-purity phosphoric acid is a key raw material for the preparation of lithium iron phosphate cathode materials. Currently, the industrial production of high-purity phosphoric acid mainly adopts the wet process, which decomposes phosphate rock with sulfuric acid and then concentrates and purifies it to obtain the target product.
[0003] In recent years, the grade of phosphate rock worldwide has gradually decreased, forcing the production of wet-process phosphoric acid to rely heavily on low-grade phosphate rock. Low-grade phosphate rock contains significantly higher levels of potassium ions than high-grade phosphate rock, resulting in excessive potassium ion concentrations in wet-process phosphoric acid products. Potassium ions occupy positions for lithium ions in the lithium iron phosphate crystal lattice, hindering lithium ion diffusion and reducing battery charge / discharge efficiency. Furthermore, excessive potassium ions can trigger side reactions in electrode materials during electrochemical cycling, leading to battery structural degradation and capacity decay. Industry standards clearly stipulate that the total alkali metal content in phosphoric acid used in batteries must not exceed 100 mg / L. Therefore, efficiently removing potassium ions from wet-process phosphoric acid is crucial for ensuring the quality of lithium iron phosphate.
[0004] Ion exchange technology has become the preferred technology for impurity removal in wet phosphoric acid processes due to its advantages such as mild operating conditions, high selectivity, and recyclable resins. However, traditional cation exchange resins are prone to structural degradation in the strongly acidic environment of high-concentration phosphoric acid, and their performance deteriorates rapidly after recycling. Furthermore, existing resins mostly focus on single active sites, failing to form a synergistic adsorption mechanism, resulting in low adsorption capacity and poor selectivity for potassium ions, making it difficult to meet the industrial-scale requirements for deep potassium removal. Therefore, finding a resin suitable for strongly acidic phosphoric acid systems and modifying it to achieve high selectivity and high efficiency in potassium ion removal has become a current focus in wet phosphoric acid processes. Summary of the Invention
[0005] To address the problems of low potassium removal efficiency, poor selectivity, and insufficient cycle stability of traditional ion exchange resins in wet-process phosphoric acid strongly acidic systems, this invention provides a method for preparing and applying ferric citrate modified Amberlyst 36 resin.
[0006] This invention is achieved through the following technical solution: a method for preparing ferric citrate modified Amberlyst 36 resin, comprising the following steps: S1. Resin pretreatment: Take Amberlyst 36 resin, rinse it repeatedly with deionized water, soak it in hydrochloric acid solution to completely convert the resin to H form; then wash it repeatedly with deionized water until the pH of the washing solution is neutral, and dry it to obtain pretreated resin. S2. Impregnation loading: The pretreated resin obtained in S1 was placed in the iron citrate alcohol dispersion, and then the surface binder was added and stirred thoroughly at room temperature; the mixture was then aged in an oven; after aging, the filtrate was removed by filtration, and the resin was repeatedly washed with deionized water until the filtrate was neutral. Finally, it was dried in an oven to obtain iron citrate modified Amberlyst 36 resin (hereinafter referred to as FeCA / A-36-H modified resin).
[0007] As a further improvement to the technical solution of the present invention, the alcohol solution in the iron citrate dispersion includes one or more of methanol, ethanol, and ethylene glycol.
[0008] As a further improvement to the technical solution of the present invention, the surface binder is a cationic titanate or a polyethyleneimine, wherein the amount of cationic titanate added is 0.5~2.0 wt% of the pretreated resin, and the amount of polyethyleneimine added is 0.5~1.0 wt% of the pretreated resin.
[0009] As a further improvement to the technical solution of the present invention, the concentration of the hydrochloric acid solution is 5~10 wt%, and the soaking time is 18~24 h.
[0010] As a further improvement to the technical solution of the present invention, the amount of ferric citrate added to the ferric citrate alcohol dispersion is 1~11 wt% of the pretreated resin, and the time for thorough stirring at room temperature after adding the surface binder is 18~24 h.
[0011] As a further improvement to the technical solution of the present invention, the aging temperature of the mixed system in the oven is 45~50°C. o C, aging time is 18~24 h.
[0012] The present invention also provides a method for preparing ferric citrate modified Amberlyst 36 resin, and the ferric citrate modified Amberlyst 36 resin prepared therefrom is used as an adsorbent for the adsorption of potassium ions in a phosphoric acid system.
[0013] As a further improvement to the application technology solution of the present invention, the phosphoric acid system is wet-process phosphoric acid.
[0014] As a further improvement to the application technology of this invention, during adsorption in wet-process phosphoric acid, ferric citrate-modified Amberlyst 36 resin is added to the wet-process phosphoric acid solution at a dosage of 3-8 g / L, and the solution is heated to 40-50 °C.o C. Stir and adsorb at 200~300 r / min for 10~20 min to complete the adsorption and removal of potassium ions in wet phosphoric acid solution.
[0015] As a further improvement to the application technology of this invention, the ferric citrate-modified Amberlyst 36 resin after adsorbing potassium ions can be desorbed and regenerated. The desorption and regeneration method is as follows: after rapidly washing the residual phosphoric acid on the resin surface with deionized water, add 10-15 wt% hydrochloric acid solution as a desorbent. The solid-liquid ratio of resin to desorbent is 0.1~0.3 g / mL. Stir at room temperature for 20~30 min to achieve potassium ion desorption and resin regeneration. After desorption, filter to separate the resin, wash with deionized water until the pH of the washing solution is neutral, and dry before reuse for potassium ion adsorption.
[0016] The present invention provides a method for preparing and applying ferric citrate-modified Amberlyst 36 resin, which has the following advantages compared with the prior art: 1. This invention uses an alcohol dispersion impregnation method to prepare ferric citrate modified Amberlyst 36 resin. The preparation process is simple, the conditions are mild, there is no secondary pollution, and it is easy to scale up industrially. By controlling the ferric citrate loading and adding a linker, the integrity of the original sulfonic acid group (-SO3H) skeleton of Amberlyst 36 resin is preserved, and carboxyl groups (-COOH) and Fe-O groups are introduced as new active sites, forming a dual-site structure of sulfonic acid group and ferric citrate active sites. This ensures the number of new active sites and avoids the agglomeration of excessive ferric citrate clogging the resin pores, thus achieving the optimal matching between the resin pore structure and active sites.
[0017] 2. The FeCA / A-36-H modified resin prepared in this invention forms a dual-active-site structure of "sulfonic acid group + iron citrate carboxyl group / Fe-O group", retaining the ion exchange function of the original sulfonic acid group, while introducing the coordination adsorption function of iron citrate, realizing the synergistic effect of ion exchange and coordination adsorption. Compared with the unmodified Amberlyst 36 resin, the static saturated adsorption capacity is increased by about 52%, the adsorption equilibrium time is shortened by 50%, and the adsorption efficiency reaches more than 90%, significantly improving the potassium ion adsorption efficiency and kinetic performance.
[0018] 3. The FeCA / A-36-H modified resin of the present invention exhibits excellent structural stability in a strongly acidic system with 50% high-concentration phosphoric acid, and its selectivity for potassium ions is significantly better than that for Na+ ions. + Ca 2+ Mg 2+ Al 3+ Coexisting impurity ions.
[0019] 4. The FeCA / A-36-H modified resin of the present invention has excellent regeneration performance. With hydrochloric acid as the desorbent, the desorption efficiency is close to 100%. Through cyclic adsorption, the potassium ion concentration in wet phosphoric acid can be reduced to about 10 mg / L, which is far superior to the industry standard. Moreover, the resin has good structural integrity during recycling and no significant loss of active sites, which greatly reduces the processing cost for industrial applications.
[0020] 5. The process method adopted in this invention is simple, relatively independent and self-contained, and can be directly connected in series with existing wet-process phosphoric acid plants to complete the technical transformation. Attached Figure Description
[0021] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This study compares the adsorption efficiency of unmodified (before loading) Amberlyst 36 resin and FeCA / A-36-H modified (after loading) resin (7 wt% ferric citrate addition) for 500 mg / L potassium ions in phosphoric acid solution. During the rapid adsorption phase (0-4 min), the FeCA / A-36-H modified resin exhibited faster adsorption kinetics. After adsorption equilibrium was reached, the adsorption efficiency of the FeCA / A-36-H modified resin was significantly higher than that of the unmodified Amberlyst 36 resin.
[0024] Figure 2 The images show the EDS spectra of FeCA / A-36-H modified resin (7 wt% ferric citrate) before and after adsorption of 500 mg / L potassium ions from phosphoric acid solution. Before potassium ion adsorption, the distribution of Fe and S elements highly overlaps, indicating successful Fe loading. After potassium ion adsorption, potassium (K) was detected, indicating successful potassium ion adsorption.
[0025] Figure 3 Fourier transform infrared spectra of Amberlyst 36 resin before and after loading ferric citrate. The presence of carboxyl groups and Fe-O bonds indicates successful loading of ferric citrate, with an added amount of ferric citrate of 7 wt%.
[0026] Figure 4Fourier transform infrared spectra of FeCA / A-36-H modified resin (7 wt% ferric citrate) before and after adsorption of 500 mg / L potassium ions in phosphoric acid solution. The appearance of KO bonds after adsorption indicates successful adsorption of potassium ions.
[0027] Figure 5 The graph shows the effect of FeCA / A-36-H modified resin (7 wt% ferric citrate addition) mass on adsorption efficiency, K + The removal efficiency in phosphoric acid solution is positively correlated with the amount of resin used. This is because the increase in the specific surface area and active site density of the resin promotes the adsorption of potassium ions.
[0028] Figure 6 A first-order kinetic (PFO) model for potassium ion adsorption in FeCA / A-36-H modified resin (7 wt% ferric citrate addition) was established.
[0029] Figure 7 A second-order kinetic (PSO) model for potassium ion adsorption in FeCA / A-36-H modified resin (7 wt% ferric citrate) was developed. The PSO model showed a better linear fit (R²). 2 =0.996), significantly higher than the PFO model, indicating that chemisorption (ion exchange and coordination) is the dominant factor controlling the adsorption rate.
[0030] Figure 8 A Boyd kinetic model was developed for the adsorption of potassium ions by FeCA / A-36-H modified resin (7 wt% ferric citrate). The fitting results showed that the linear equation (Y=0.3195X-0.5548) did not pass through the origin, indicating that intraparticle diffusion is not the only rate-controlling step, and liquid film diffusion also plays a role in the adsorption process.
[0031] Figure 9 An IPD kinetic model for potassium ion adsorption in FeCA / A-36-H modified resin (7 wt% ferric citrate). Adsorption capacity q t With t 1 / 2 The relationship exhibits two linear segments: the first segment is the initial stage (rapid adsorption), corresponding to the diffusion of ions from the solution to the liquid film on the resin surface; the second segment is the adsorption near equilibrium stage, corresponding to the diffusion of ions within the particles in the resin channels.
[0032] Figure 10The effect of temperature on the adsorption efficiency of FeCA / A-36-H modified resin (7 wt% ferric citrate) on potassium ions in phosphoric acid solution (500 mg / L) was investigated. The adsorption efficiency initially increased and then decreased with increasing temperature. Moderate heating reduced the viscosity of the phosphoric acid solution, thus accelerating the diffusion rate of potassium ions and promoting contact between the resin's active sites and potassium ions. However, excessively high temperatures may cause the ferric citrate to dissociate from the resin and damage the resin's functional groups, resulting in a significant decrease in adsorption efficiency.
[0033] Figure 11 (a) Effect of phosphoric acid concentration on the adsorption efficiency of FeCA / A-36-H modified resin (7 wt% ferric citrate) on potassium ions in phosphoric acid solution at 500 mg / L. Due to the large amount of H+ present in high-concentration phosphoric acid solutions... + It competes with potassium ions for active adsorption sites on the resin surface, and the strongly acidic environment protonates the sulfonic acid groups, weakening their attraction to potassium. + The selective binding ability of the adsorption capacity is reduced, which leads to a significant decrease in adsorption performance. Figure 11 (b) is a linear fit of the distribution coefficient Kd with the logarithm of the molar concentration, and the coefficient of determination (R²) 2 =0.974), indicating that the two have a good linear correlation.
[0034] Figure 12 The adsorption efficiency of FeCA / A-36-H modified resin (7 wt% ferric citrate) for a single cation is given.
[0035] Figure 13 To simulate the concentration of each metal ion in a multi-metal ion coexistence system after adsorption by FeCA / A-36-H modified resin (7 wt% ferric citrate).
[0036] Figure 14 To investigate the effect of different hydrochloric acid concentrations on the desorption efficiency of the resin, it was found that as the hydrochloric acid concentration increased, the desorption efficiency first increased and then decreased, reaching its maximum when the hydrochloric acid concentration reached 12%.
[0037] Figure 15 Ten adsorption-desorption cycle experiments were conducted on FeCA / A-36-H modified resin (7 wt% ferric citrate addition). The adsorption efficiency and adsorption capacity of the resin for potassium ions were relatively stable, further demonstrating that FeCA / A-36-H modified resin (7 wt% ferric citrate addition) has good cycle stability. Detailed Implementation
[0038] To better understand the above-mentioned objectives, features, and advantages of the present invention, the solutions of the present invention will be further described below. It should be noted that, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other.
[0039] Many specific details are set forth in the following description in order to provide a full understanding of the invention, but the invention may also be practiced in other ways different from those described herein; obviously, the embodiments in the specification are only some embodiments of the invention, and not all embodiments.
[0040] This invention provides a specific embodiment of a method for preparing ferric citrate modified Amberlyst 36 resin, comprising the following steps: S1. Resin pretreatment: Take Amberlyst 36 resin, rinse it repeatedly with deionized water, soak it in hydrochloric acid solution to completely convert the resin to H form; then wash it repeatedly with deionized water until the pH of the washing solution is neutral, and dry it to obtain pretreated resin. S2. Impregnation loading: The pretreated resin obtained in S1 is placed in the iron citrate alcohol dispersion, and then a surface binder is added. The mixture is stirred thoroughly at room temperature to allow the iron citrate to be fully adsorbed onto the resin surface and into the pores. The mixture is then aged in an oven. After aging, the filtrate is removed by filtration, and the resin is repeatedly washed with deionized water until the filtrate is neutral. Finally, the resin is dried in an oven to obtain iron citrate modified Amberlyst 36 resin.
[0041] In step S1, the purpose of repeatedly rinsing with deionized water is to remove obvious impurities; the purpose of soaking in hydrochloric acid solution is to remove metal impurities and residual organic matter from the resin surface and pores, and at the same time to completely convert the resin into H-type.
[0042] In step S2 of this invention, the purpose of aging the mixed system in an oven is to enhance the binding stability of the iron aluminate citrate resin.
[0043] In one example provided by the present invention, the alcohol solution in the iron citrate alcohol dispersion includes one or more of methanol, ethanol, and ethylene glycol. The preparation method of the iron citrate alcohol dispersion is as follows: iron citrate (C6H5FeO7) is dispersed in an alcohol solution in a certain proportion, and stirred at 200 r / min for 1-2 h at room temperature to uniformly disperse iron citrate in the alcohol solution, thereby obtaining the iron citrate alcohol dispersion.
[0044] In another example provided by the present invention, the surface binder is a cationic titanate or polyethyleneimine, wherein the amount of cationic titanate added is 0.5 to 2.0 wt% of the pretreated resin, and the amount of polyethyleneimine added is 0.5 to 1.0 wt% of the pretreated resin.
[0045] In one example provided by the present invention, the concentration of the hydrochloric acid solution is 5-10 wt%, and the soaking time is 18-24 h.
[0046] In another example provided by the present invention, the amount of ferric citrate added to the ferric citrate alcohol dispersion is 1 to 11 wt% of the pretreated resin, and the time for thorough stirring at room temperature after adding the surface binder is 18 to 24 h.
[0047] In one example provided by the present invention, the aging temperature of the mixture system in an oven is 45-50°C. o C, aging time is 18~24 h.
[0048] The present invention also provides a method for preparing ferric citrate modified Amberlyst 36 resin, and the ferric citrate modified Amberlyst 36 resin prepared therefrom is used as an adsorbent for the adsorption of potassium ions in a phosphoric acid system.
[0049] Furthermore, the phosphoric acid system is wet-process phosphoric acid.
[0050] In one example provided by this invention, during adsorption in wet-process phosphoric acid, ferric citrate-modified Amberlyst 36 resin is added to the wet-process phosphoric acid solution at a dosage of 3-8 g / L, and the solution is heated to 40-50 °C. o C. Stir and adsorb at 200~300 r / min for 10~20 min to complete the adsorption and removal of potassium ions in wet phosphoric acid solution.
[0051] In another example provided by the present invention, the ferric citrate-modified Amberlyst 36 resin after adsorbing potassium ions can be desorbed and regenerated. The desorption and regeneration method is as follows: after rapidly washing the residual phosphoric acid on the resin surface with deionized water, 10-15 wt% hydrochloric acid solution is added as a desorbent, the solid-liquid ratio of resin to desorbent is 0.1~0.3 g / mL, and the resin is stirred at room temperature for 20~30 min to achieve potassium ion desorption and resin regeneration; after desorption, the resin is filtered to separate it, washed with deionized water until the pH of the washing solution is neutral, and dried before being used again for potassium ion adsorption.
[0052] The specific embodiments of the present invention will be described in detail below.
[0053] Example 1: Preparation of FeCA / A-36-H resins with different loadings (1) Resin pretreatment: Take 20 g of Amberlyst 36 resin, rinse it repeatedly with deionized water, and then soak it in 5 wt% hydrochloric acid solution for 24 h to remove metal impurities and residual organic matter on the resin surface, while ensuring that the resin is completely converted to the hydrogen form. Then wash it repeatedly with deionized water until the pH of the washing solution is neutral. Finally, place the resin in a vacuum drying oven and dry it at 50℃ for 24 h for later use to obtain A-36-H.
[0054] (2) Loading modification: A certain amount of ferric citrate (1 wt%, 3 wt%, 5 wt%, 7 wt%, 9 wt%, and 11 wt% respectively) was weighed and dispersed in 50 mL of 40% ethanol solution. The mixture was stirred at room temperature for 1 h to ensure complete dispersion. Then, 20 g of pretreated A-36-H resin was weighed and added to the above ferric citrate dispersion, and 0.5 wt% polyethyleneimine was added and stirred thoroughly for 24 h.
[0055] (3) Post-loading treatment: The stirred mixture was filtered to obtain solid resin, which was repeatedly washed with deionized water until the filtrate was neutral. Then it was dried in an oven at 50℃ for 12 h to obtain FeCA / A-36-H modified resins with different iron citrate loadings.
[0056] 2. Adsorption performance test The adsorption performance of the resin for potassium ions in phosphoric acid was tested using a static adsorption method. A quantitative amount of resin was added to potassium ion solutions (solvent: 50 wt% phosphoric acid) with concentrations of 300 mg / L, 500 mg / L, and 700 mg / L, respectively, and adsorption was performed by stirring at 200 r / min at a set temperature. The changes in potassium ion concentration in the solution were measured using an ion meter (PXSJ-216F, equipped with a PK-1-01 type potassium ion electrode and a 217-01 type reference electrode).
[0057] Example 2: Adsorption process optimization experiment (1) Effect of resin dosage: At 298 K, the effect of different masses (1-12 g) of FeCA / A-36-H modified resin (7 wt% ferric citrate) on adsorption efficiency was investigated, such as Figure 5 As shown in the figure. The results indicate that the adsorption efficiency significantly improves when the resin dosage increases from 1 g to 5 g; however, the increase in adsorption efficiency slows down when the dosage is further increased to 12 g. Considering both adsorption capacity and cost, the optimal resin dosage was determined to be 5 g.
[0058] (2) Adsorption time and kinetics: such as Figures 6-9As shown, the adsorption kinetics of potassium ions by FeCA / A-36-H modified resin (7 wt% ferric citrate) was investigated at 298 K. The results showed that the adsorption process consisted of a rapid adsorption phase (0–10 min) and a slow equilibrium phase (10–20 min). Compared with unmodified A-36-H resin, the adsorption rate of FeCA / A-36-H modified resin was significantly improved, reaching an adsorption efficiency of over 90% at 10 min, and the equilibrium time was shortened to 10 min.
[0059] (3) Temperature effect: such as Figure 10 As shown, the adsorption efficiency of FeCA / A-36-H modified resin (7wt% ferric citrate) for potassium ions was investigated at different temperatures (293-343 K). The results showed that the adsorption efficiency first increased and then decreased with increasing temperature, reaching a peak of 94.9% at 313 K (40℃).
[0060] (4) Effect of phosphoric acid concentration: such as Figure 11 As shown in (a) and (b), the effect of phosphoric acid concentration (0 M-14 M) on the adsorption efficiency of FeCA / A-36-H modified resin (7 wt% ferric citrate) was investigated. The results showed that the adsorption efficiency decreased significantly with increasing phosphoric acid concentration, indicating that high concentrations of H⁺ compete with K⁺ for active sites.
[0061] (5) Selectivity of impurity ion adsorption: In a simulated wet-process phosphate polymetallic ion coexistence system, the adsorption of Na+ by FeCA / A-36-H resin was studied. + K + Ca 2+ Mg 2+ Al 3+ The adsorption selectivity of metal ions, such as... Figure 12 As shown, the initial concentration of each metal ion in the solution before adsorption was 500 mg / L. After adsorption by the resin, the adsorption efficiency of different ions showed significant differences. Specifically, the K⁺ concentration decreased dramatically from approximately 500 mg / L to below approximately 50 mg / L, with a removal rate approaching 90%, demonstrating extremely strong selective adsorption capacity. Meanwhile, the Na⁺ concentration decreased significantly. + Ca 2+ Mg 2+ Al 3+ Although the plasma concentration decreased to some extent, it remained above 300 mg / L, and the removal rate was significantly lower than that of K. + . Figure 13To simulate the concentration of each metal ion after adsorption by the resin in a multi-metal ion coexistence system, it was observed that even when all impurity ions coexist at a uniform concentration (500 mg / L), the FeCA / A-36-H resin still exhibits good selectivity for potassium ions. The partition coefficients (K0) of the FeCA / A-36-H resin for each metal ion were calculated. d (See Table 1). Calculate the selectivity coefficients (K0) of FeCA / A-36-H resin for each metal ion. A / B (See Table 2). A comprehensive analysis shows that the selectivity of FeCA / A-36-H resin for each ion follows the order K... + >Al 3+ >Na + >Mg 2+ >Ca 2+ .
[0062] Table 1. Partition coefficients of FeCA / A-36-H resin for metal ions
[0063] Table 2. Relative selectivity coefficients of FeCA / A-36-H resin for metal ion adsorption.
[0064] Example 3: Desorption and Regeneration Experiment During adsorption in wet-process phosphoric acid, ferric citrate-modified Amberlyst 36 resin (7 wt% ferric citrate in Example 1) was added to the wet-process phosphoric acid solution at a resin dosage of 5 g / L, and the solution was heated to 40 °C. o C. Stir and adsorb at 200 r / min for 20 min to complete the adsorption and removal of potassium ions from wet phosphoric acid solution.
[0065] During desorption and regeneration, residual phosphoric acid on the resin surface is quickly washed with deionized water, and then 12 wt% hydrochloric acid solution is added as a desorbent. The solid-liquid ratio of resin to desorbent is 0.2 g / mL. The resin is stirred at room temperature for 20 min to achieve potassium ion desorption and resin regeneration. After desorption, the resin is separated by filtration, washed with deionized water until the pH of the washing solution is neutral, and dried before being reused for potassium ion adsorption.
[0066] (1) Desorbent screening: such as Figure 14 As shown, 5%, 8%, 10%, 12%, and 15% hydrochloric acid were used to desorb the adsorbed FeCA / A-36-H modified resin (7 wt% ferric citrate addition). The results showed that 12% hydrochloric acid had the best desorption effect, with a desorption efficiency close to 100%.
[0067] (2) Cyclic stability: such as Figure 15The FeCA / A-36-H resin (7 wt% ferric citrate) was subjected to 10 adsorption-desorption cycle experiments. The results showed that after 10 cycles, the adsorption efficiency remained above 82%, and the adsorption capacity retention rate exceeded 90%, demonstrating its good cycle stability.
[0068] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the present invention. Although detailed descriptions have been provided with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments, and they should all be covered within the protection scope of the claims.
Claims
1. A method for preparing ferric citrate modified Amberlyst 36 resin, characterized in that, Includes the following steps: S1. Resin pretreatment: Take Amberlyst 36 resin, rinse it repeatedly with deionized water, soak it in hydrochloric acid solution to completely convert the resin to H form; then wash it repeatedly with deionized water until the pH of the washing solution is neutral, and dry it to obtain pretreated resin. S2. Impregnation loading: The pretreated resin obtained in S1 was placed in the iron citrate alcohol dispersion, and then the surface binder was added and stirred thoroughly at room temperature; the mixture was then aged in an oven; after aging, the filtrate was removed by filtration, and the resin was repeatedly washed with deionized water until the filtrate was neutral. Finally, it was dried in an oven to obtain iron citrate modified Amberlyst 36 resin.
2. The method for preparing ferric citrate modified Amberlyst 36 resin according to claim 1, characterized in that, The alcohol solution in the iron citrate dispersion includes one or more of methanol, ethanol, and ethylene glycol.
3. The method for preparing ferric citrate modified Amberlyst 36 resin according to claim 1, characterized in that, The surface binder is a cationic titanate or a polyethyleneimine, wherein the amount of cationic titanate added is 0.5 to 2.0 wt% of the pretreated resin, and the amount of polyethyleneimine added is 0.5 to 1.0 wt% of the pretreated resin.
4. The method for preparing ferric citrate modified Amberlyst 36 resin according to claim 1, characterized in that, The concentration of the hydrochloric acid solution is 5-10 wt%, and the soaking time is 18-24 h.
5. The method for preparing ferric citrate modified Amberlyst 36 resin according to claim 1, characterized in that, The amount of ferric citrate added to the ferric citrate alcohol dispersion is 1-11 wt% of the pretreated resin, and the time for thorough stirring at room temperature after adding the surface binder is 18-24 h.
6. The method for preparing ferric citrate modified Amberlyst 36 resin according to claim 1, characterized in that, The mixing system is aged in an oven at a temperature of 45-50°C. o C, aging time is 18~24 h.
7. The ferric citrate-modified Amberlyst 36 resin prepared by the method described in any one of claims 1 to 6 is used as an adsorbent for the adsorption of potassium ions in a phosphoric acid system.
8. The application as described in claim 7, characterized in that, The phosphoric acid system is a wet-process phosphoric acid.
9. The application as described in claim 8, characterized in that, During adsorption in wet-process phosphoric acid, ferric citrate-modified Amberlyst 36 resin is added to the wet-process phosphoric acid solution at a dosage of 3-8 g / L, and the solution is heated to 40-50 °C. o C. Stir and adsorb at 200~300 r / min for 10~20 min to complete the adsorption and removal of potassium ions in wet phosphoric acid solution.
10. The application as described in claim 7, characterized in that, The ferric citrate-modified Amberlyst 36 resin after adsorbing potassium ions can be desorbed and regenerated. The desorption and regeneration method is as follows: after rapidly washing the residual phosphoric acid on the resin surface with deionized water, add 10-15 wt% hydrochloric acid solution as a desorbent. The solid-liquid ratio of resin to desorbent is 0.1~0.3 g / mL. Stir at room temperature for 20~30 min to desorb potassium ions and regenerate the resin. After desorption is complete, filter and separate the resin, wash with deionized water until the pH of the washing solution is neutral, and then dry it before using it again for potassium ion adsorption.